Filsafat Pendidikan Progresivisme dalam Kurikulum Pendidikan Bahasa Indonesia - Istifatun Zaka (Indonesian Journal of Teaching and Teacher Education, 2022)
This paper discusses the philosophy of progressivism in the Indonesian language education curriculum. Education development in Indonesia cannot be separated from various foundations, especially in the flow of philosophy in implementing education. One of them is the educational philosophy of progressivism which underlies various aspects of education. For this reason, it is necessary to study how the philosophy of progressivism has contributed to the Indonesian language education curriculum. This research is a descriptive qualitative method. The research was conducted using library research by searching for previous literature. The research was conducted by examining relevant references related to the philosophy of language, the philosophy of progressivism, and the language education curriculum in Indonesia. The results show that the philosophy of progressivism contributes to the language curriculum, starting from the syllabus, methodology, strategies for dealing with individual differences, assessment, research, and evaluation. In addition, the development of philosophical thinking about language affects the practice of language teaching in Indonesia, namely the existence of Indonesian language teaching based on traditional linguistics, structural linguistics, and systemic functional linguistics.